The Relationship between Parental Involvement and Learning Motivation with Science Learning Achievement of Public Junior High School Students in Kendari City - Adinda Maharani; Muhiddin Palennari; Muhammad Arsyad; Firdaus Daud; Halimah Husain (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to analyze the relationship between parental involvement and learning motivation with students’ science (IPA) achievement in public junior high schools in Kendari City. This research employed an ex post facto design with a survey approach and correlational design. The sample consisted of 178 eighth-grade students selected using multistage proportional sampling. Data were collected through questionnaires and report card documentation, and analyzed using descriptive statistics and simple as well as multiple linear regression. The results showed that parental involvement, learning motivation, and science achievement were generally in the moderate category. There was a positive and significant relationship between parental involvement and science achievement (53.70%), as well as between learning motivation and science achievement (72.40%). Simultaneously, both variables showed a positive and significant relationship with a contribution of 72.50%, with learning motivation being the more dominant variable.